Pectoralis Major Tendon Repair: Transosseous Suture Technique - John W. Belk BA; Jonathan T. Bravman MD; Rachel M. Frank MD; Adam J. Seidl MD; Eric C. McCarty MD (SAGE Publishing, 2023)
Background: Pectoralis major ruptures are rare injuries that occur in young men between 20 and 40 years of age, typically during resistance training in the eccentric phase of muscle contraction. As the incidence of these ruptures increases with increasing activity levels and use of anabolic steroids, it is important to understand effective repair techniques. Indications: Repair of the ruptured pectoralis major tendon is indicated for young, active patients seeking to regain full functionality of the affected upper extremity. Technique Description: In short, after the pectoralis major is identified, the insertion site is revealed just lateral to the biceps tendon. The site for the bone trough is then exposed through cauterization of superficial tissue, and a cortical bone trough is drilled vertically using a small round burr. The location of 3 pilot holes is identified just lateral to the cortical bone trough, and then the holes are drilled to allow for placement of the anchors later in the procedure. The tendon itself is then identified, and sutures are placed in the bulk of the muscle tendon in a Krackow fashion. After the tendon is properly sutured, it is placed under tension to test the structural integrity of the suture pattern and ensure proper load capacity. The sutures are then passed through the pilot holes, the tendon is pulled down into the trough, and the sutures are tied down to the bone. Results: After an appropriate rehabilitation protocol is followed for up to 6 months postoperatively, the transosseous suture technique in the context of pectoralis major tendon repairs allows for adequate tissue to bone healing and near-complete restoration of patient functionality and strength. Conclusion: Acute repair of pectoralis major tendon tears using a transosseous suture technique is effective in restoring upper extremity strength and functionality and is associated with high patient satisfaction. The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.